2021
DOI: 10.1111/head.14191
|View full text |Cite
|
Sign up to set email alerts
|

Narrative review of neuroimaging in migraine with aura

Abstract: Objective To improve the understanding of the role and utility of various neuroimaging modalities (clinical and research) for the evaluation of migraine aura (MA) and hemiplegic migraine during the ictal and interictal phases. Background MA is defined by reversible neurologic symptoms and is considered a manifestation of a primary condition. As such, most patients with MA do not require imaging. However, if there are atypical features, change in symptom pattern, or it is a first‐time presentation, neuroimaging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…This indicates that migraine and stroke may be a part of a spectrum of vascular complications in a group of patients with comorbid vascular conditions [ 34 ]. Imaging techniques such as SPECT [ 35 ] may result in the development of novel diagnostic and therapeutic interventions to improve quality of life for patients with migraine. This study demonstrated the usefulness of SPECT in assessing vascular changes.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that migraine and stroke may be a part of a spectrum of vascular complications in a group of patients with comorbid vascular conditions [ 34 ]. Imaging techniques such as SPECT [ 35 ] may result in the development of novel diagnostic and therapeutic interventions to improve quality of life for patients with migraine. This study demonstrated the usefulness of SPECT in assessing vascular changes.…”
Section: Discussionmentioning
confidence: 99%
“…The insula was associated with the different aspects of sensorimotor and cognitive control of speech production ( Schwedt et al, 2015 ; Battistella et al, 2018 ). The precentral gyrus was the traditional movement-related higher cortex and included the primary motor area, the somatomotor cortex, and the lateral premotor area ( Meier et al, 2008 ; Arca et al, 2021 ). The prefrontal cortex was the central brain region for executive functions ( Ueda et al, 2018 ; Ashina et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…These results could be able to intuitively explain the cumulative therapeutic effect of acupuncture treatment. the right middle frontal gyrus, the left insula, the precentral gyrus, the right supramarginal gyrus, the left Middle occipital gyrus, and the right thalamus were related with pain matrix network, visual domain, sensorimotor domain, cognitive-control domain, and default mode domain [36][37][38][39][40]. It was also shown that the cumulative therapeutic effects of acupuncture treatment in migraine could be regarded as the consequence of interactions between pain modulation and cortical networks, which might provide an objective reference of treatment in migraine.…”
Section: Discussionmentioning
confidence: 99%